Immune histories and natural infection protection during the omicron era - Hiam Chemaitelly; Houssein H. Ayoub; Niklas Bobrovitz; Peter Coyle; Patrick Tang; Mohammad R. Hasan; Hadi M. Yassine; Asmaa A. Al Thani; Zaina Al-Kanaani; Einas Al-Kuwari; Andrew Jeremijenko; Anvar Hassan Kaleeckal; et al. (Communications Medicine)
Abstract Background Past immunological events can either enhance or compromise an individual’s future immune protection. This study investigated how different severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) natural infection histories before an omicron infection, with or without vaccination, influence protection against subsequent omicron reinfection. Methods Three national, matched, retrospective cohort studies were conducted in Qatar from February 28, 2020, to August 12, 2024 to compare incidence of omicron reinfection between individuals with two omicron infections (omicron double-infection cohort) and those with one (omicron single-infection cohort); the omicron double-infection cohort with individuals who had a pre-omicron infection followed by an omicron reinfection (pre-omicron-omicron double-infection cohort); and the pre-omicron-omicron double-infection cohort with the omicron single-infection cohort. Results Here we show that, in the first study, comparing the omicron double-infection cohort to the omicron single-infection cohort, the adjusted hazard ratio (aHR) is 1.27 (95% CI: 1.13–1.43); 0.93 (95% CI: 0.68–1.28) for the unvaccinated and 1.34 (95% CI: 1.18–1.52) for the vaccinated. In the second study, comparing the omicron double-infection cohort to the pre-omicron-omicron double-infection cohort, the aHR is 1.37 (95% CI: 1.13–1.65); 1.12 (95% CI: 0.63–1.97) for the unvaccinated and 1.42 (95% CI: 1.16–1.74) for the vaccinated. In the third study, comparing the pre-omicron-omicron double-infection cohort to the omicron single-infection cohort, the aHR is 0.97 (95% CI: 0.92–1.03); 0.75 (95% CI: 0.66–0.85) for the unvaccinated and 1.03 (95% CI: 0.97–1.09) for the vaccinated. Conclusions Immune history shapes protection against omicron reinfection, with pre-omicron-omicron immunity enhancing protection, while repeated similar exposures reduce protection against new variants.